Evidence on article 5.3 of FCTC (tobacco industry interference in tobacco control activities) in India- a qualitative scoping study - Sonu Goel (BMC Public Health, 2021)
Abstract: Background: The Tobacco Industry (henceforth TI) yearns to portray itself as being “socially responsible” and fights for the decision-making positions; that are it used to deter, delay or dilute tobacco control measures. There is little documented evidence of Tobacco Industry Interference (henceforth TII) from India, the scope of their interference and challenges faced by the experts for effective tobacco control. This research study seeks to cover this significant gap in the literature on the TI of India. Methods: A cross-sectional qualitative research design, based upon in-depth interviews (N = 26), was used to explore the key stakeholders’ opinions regarding TII in India. The interviews used a set of questions to collect information about the participant’s roles and responsibilities in tobacco control, the nature of TII faced by the participants, means of influence by TI, barriers and challenges to tobacco control efforts. Results: Most of the respondents were engaged in tobacco control, training, advocacy and awareness generation activities for 5–10 years or more. The respondents defined the TI and its scope as per their experience with the help of the power ranking methodology. Most of them perceived TI as ‘manufacturers’ while others consider them as ‘advertisers’, ‘public relation companies’, ‘wholesalers’, ‘vendors’, and ‘Government firms with TI stocks. The research team identified six significant domains: influencing the policy and administrative decisions, Interference in the implementation of tobacco control laws and activities, false propaganda and hiding the truth, manipulating front action groups (FAG), rampant tobacco advertising and promotion activities and others under which TII activities were classified. Most respondents believed that TI players were interfering in the policy decisions, implementing the tobacco control laws and activities and manipulating the FAG. A detailed taxonomic classification of the TII strategies that emerged from our analysis was linked to article 5.3 of FCTC. Conclusions: The study documented a significant level of TII in different domains, with stakeholders acting at various hierarchical levels. Thus providing insight into the tactics of the TI in order to enable stakeholders to anticipate and pre-empt the kinds of alliances the TI may attempt to build; stimulating academicians and researchers to undertake in-depth analysis into various strategies and therefore underscoring the need to ensuring transparency in official interaction with the TI and its representatives.